Current ozone levels threaten gross primary production and yield of Mediterranean annual pastures and nitrogen modulates the response - Calvete-Sogo, Héctor; Elvira, Susana; Sanz, Javier; González-Fernández, Ignacio; García-Gómez, Héctor; Sánchez-Martín, Laura; Alonso, Rocío; Bermejo-Bermejo, Victoria (Atmospheric Environment, 2014)
Pastures are among the most important ecosystems in Europe considering their biodiversity and distribution area. However, their response to increasing tropospheric ozone (O3) and nitrogen (N) deposition, two of the main drivers of global change, is still uncertain. A new Open-Top Chamber (OTC) experiment was performed in central Spain, aiming to study annual pasture response to O3 and N in close to natural growing conditions. A mixture of six species of three representative families was sowed in the field. Plants were exposed for 40 days to four O3 treatments: filtered air, non-filtered air (NFA) reproducing ambient levels and NFA supplemented with 20 and 40 nl l-1 O3. Three N treatments were considered to reach the N integrated doses of “background”, +20 or +40 Kg N ha-1. Ozone significantly reduced green and total aboveground biomass (maximum reduction 25%) and increased the senescent biomass (maximum increase 40%). Accordingly, O3 decreased community Gross Primary Production due to both a global reduction of ecosystem CO2 exchange and an increase of ecosystem respiration. Nitrogen could partially counterbalance O3 effects on aboveground biomass when the levels of O3 were moderate, but at the same time O3 exposure reduced the fertilization effect of higher N availability. Therefore, O3 must be considered as a stress factor for annual pastures in the Mediterranean areas.
Keywords: annual grasslands interactions; Critical levels; Dehesa; Global change; nitrogen; tropospheric ozone

Tools for determining critical levels of atmospheric ammonia under the influence of multiple disturbances - Pinho, P; Llop, E; Ribeiro, M C; Cruz, C; Soares, A; Pereira, M J; Branquinho, C (Environmental Pollution, 2014)
Critical levels (CLEs) of atmospheric ammonia based on biodiversity changes have been mostly calculated using small-scale single-source approaches, to avoid interference by other factors, which also influence biodiversity. Thus, it is questionable whether these CLEs are valid at larger spatial scales, in a multi- disturbances context. To test so, we sampled lichen diversity and ammonia at 80 sites across a region with a complex land-cover including industrial and urban areas. At a regional scale, confounding factors such as industrial pollutants prevailed, masking the CLEs. We propose and use a new tool to calculate CLEs by stratifying ammonia concentrations into classes, and focusing on the highest diversity values. Based on the significant correlations between ammonia and biodiversity, we found the CLE of ammonia for Mediterranean evergreen woodlands to be 0.69 mgm?3, below the previously accepted value of 1.9 mgm?3, and below the currently accepted pan-European CLE of 1.0 mgm?3
Keywords: Air Pollutants; Air Pollutants: analysis; ammonia; Ammonia: analysis; Atmosphere; Atmosphere: chemistry; Biodiversity; Critical thresholds; Environmental Monitoring; Environmental Monitoring: methods; Eutrophication; Functional groups; Global change; lichens; Lichens: chemistry; Lichens: classification; nitrogen

Growth projections reveal local vulnerability of Mediterranean oaks with rising temperatures - Gea-Izquierdo, Guillermo; Fernández-de-Uña, Laura; Cañellas, Isabel (Forest Ecology and Management, 2013)
Growth projections using ecological models fitted to data collected along climatic gradients can help to understand how forests will respond to climate change. Stem growth of two Mediterranean oaks was predicted using nonlinear multiplicative models as a function of precipitation and minimum temperature of the hydrological year fitted to dendrochronological data. The growth of both species increased nonlinearly with accumulated precipitation before reaching an asymptote, but the species with a warmer niche (Q. ilex, an evergreen species) required lower levels of precipitation to achieve high relative growth. The species-specific relationship between growth and minimum temperature exhibited an optimum for the two species. Trees were negatively affected by high minimum temperatures whereas they responded negatively (Q. ilex) or neutrally (Q. pyrenaica, a deciduous species) to low temperatures along the climatic gradient analyzed. Growth would decrease rapidly when minimum temperatures rose above approximately 7 °C for Q. pyrenaica and 9 °C for Q. ilex. Most growth projections suggest a likely future decrease in productivity along the species range for Q. pyrenaica and particularly at species-specific warm, dry locations pointed to a future drastic reduction in productivity as a result of the increase in temperatures without a paired increase in precipitation forecasted by the different climate scenarios considered. In agreement with results from studies modeling future distribution of species this suggests that Q. pyrenaica could be threatened by climate change at the species local dry edge where, in addition, stands often present a lack of seed regeneration. More drought tolerant Q. ilex might profit from warming temperatures at cold northern locations but would also reduce productivity at warm, dry locations. Stem growth was successfully modeled using biologically meaningful species-specific responses to climate which provided key ecological information to understand the functional response of the two species. The models used have much potential to be applied with dendroecological data to study the response of forests to climate change.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Dendroecology; Forest decline; Global change; Nonlinear response; Quercus ilex; Quercus pyrenaica

Positive cascade effects of forest fragmentation on acorn weevils mediated by seed size enlargement - Bonal, Raul; HERNÁNDEZ, MARISA; ORTEGO, JOAQUÍN; Muñoz, Alberto; ESPELTA, JOSEP M. (Insect Conservation and Diversity, 2012)
Abstract. 1. Today, forest fragmentation is one of the major threats to biodiversity worldwide. In this context, fragmented populations of specialised forest organisms face an increasing risk of extinction because of factors such as local food scarcity. Nonetheless, the role of food availability may differ depending on organism size, which is expected to determine the energy requirements and mobility between fragments. 2. A field study was carried out on Curculio elephas, a forest beetle with low dispersal potential, whose larval development takes place in oak Quercus spp. acorns. 3. For a similar seed crop per tree, acorn size was larger in isolated oaks than in trees located in forest patches. Thus, fragmentation increased local food availability for C. elephas. Larger acorns enabled larval size to increase, a key fitness proxy associated with individual survival, adult size, and potential female fecundity. Indeed, the number of both adults and larvae was higher in isolated trees than in forest patches. 4. In the current scenario of increasing forest fragmentation, the survival likelihood of specialist insects may strongly depend on their ability to adapt to altered environmental conditions. To the best of our knowledge, this is the first study to report on how some forest insects may take advantage of fragmentation-mediated changes to survive in isolated trees. 5. From a conservation perspective, management policies should preserve isolated trees as a source of seeds and fauna for the natural regeneration of forest ecosystems after unproductive farmlands have been abandoned.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn size; Curculio; Forest fragmentation; forest insects; Global change; individual fitness; larval size

Ectomycorrhizal communities in a Mediterranean forest ecosystem dominated by Quercus ilex: seasonal dynamics and response to drought in the surface organic horizon - Richard, Franck; Roy, Melanie; Shahin, Oula; Sthultz, Christopher; Duchemin, Myriam; Joffre, Richard; Selosse, Marc-André (Annals of Forest Science, 2011)
• Introduction Millions of hectares of Quercus ilex forests dominate disturbed landscapes in the western part of the Mediterranean basin. Although these forests are very widespread, little is known about the composition and structure of their associated ectomycorrhizal fungal communities. • Results and discussion We examined seasonal patterns in ectomycorrhizal communities and their response to increased drought using a rainfall exclusion experiment established in a Q. ilex coppice since 2003. Ectomycorrhizae were sampled four times in 2007–2009. By sequencing fungal ITS, we identified 129 species in 1,147 sequenced ectomycorrhizal root tips. The fungal community in the surface organic horizon was well described by the logseries theoretical model, with 47.9% of singleton species. The composition of the community was strongly dominated by Basidiomycetes, with three families (Thelephoraceae, Russulaceae and Cortinariaceae) accounting for 72.9% of the root tips. Relative abundance of Russulaceae and Thelephoraceae showed pronounced seasonal shifts. Experimental reduction of rainfall resulted in significant shifts in community composition and seasonal fluctuations but had no effect on global richness of the community. • Conclusions Together, these results suggest that the predicted rainfall reduction in this region due to climate change will lead to shifts
Keywords: Drought; ectomycorrhizal communities; Global change; Mediterranean forests

Using lichen functional diversity to assess the effects of atmospheric ammonia in Mediterranean woodlands - Pinho, Pedro; Dias, Teresa; Cruz, Cristina; Sim Tang, Y; Sutton, Mark A; Martins-Loução, Maria-Amélia; Máguas, Cristina; Branquinho, Cristina (Journal of Applied Ecology, 2011)
1. Atmospheric ammonia (NH3) is one of the main drivers for ecosystem changes world-wide, including biodiversity loss. Modelling its deposition to evaluate its impact on ecosystems has been the focus of many studies. For that, universal indicators are needed to determine and compare the early effects of NH3 across ecosystems. 2. We evaluate the effects of atmospheric NH3 in ecosystems using lichens, which are one of the most sensitive communities at the ecosystem level. Rather than measuring total diversity, we use a functional diversity approach because this is potentially a more universal tool. 3. We evaluated the spatial and temporal patterns of atmospheric NH3 concentrations ([NH3]atm) emitted from a point-source over a 1-year period in a cork oak Mediterranean woodland. We observed a temporal pattern of [NH3]atm, with maximum concentrations during autumn. 4. The distribution of lichen species was c. 90% explained by [NH3]atm. The tolerance of lichen species to atmospheric NH3, based on expert knowledge from literature, was tested for the first time against direct measurements of atmospheric NH3. Most species were well classified, with the exception of Lecanora albella and Chrysothrix candelaris, which were more tolerant than expected. Our updated lichen classification can be used to establish lichen functional groups that respond to atmospheric NH3, and these can be used in other Mediterranean countries. 5. Increasing [NH3]atm led to a complete replacement of oligotrophic by nitrophytic species within 65 m of the NH3 source. The geostatistical analysis of functional diversity variables yielded a spatial model with low non-spatial variance, indicating that these variables can cope robustly with high spatial variation in NH3. 6. Synthesis and applications. Our results support the use of functional diversity variables, such as a lichen diversity value, as accurate and robust indicators of the effects of atmospheric NH3 on ecosystems. The spatial modelling of these indicators can provide information with high spatial resolution about the effects of atmospheric NH3 around point- and diffuse sources. As this methodology is based on functional groups, it can be applied to monitor both the impact of atmospheric NH3 and the success of mitigation strategies.
Keywords: Agriculture; atmospheric NH3; biodiversity loss; Cattle; Ecological indicators; Global change; spatial analysis

Forest pathogens with higher damage potential due to climate change in Europe - La Porta, N; Capretti, P; Thomsen, I M; Kasanen, R; Hietala, A M; Von Weissenberg, K (Canadian Journal of Plant Pathology, 2008)
Abstract Most atmospheric scientists agree that climate changes are going to increase the mean temperature in Europe with increased frequency of climatic extremes, such as drought, floods, and storms. Under such conditions, there is high probability that forests will be subject to increased frequency and intensity of stress due to climatic extremes. Therefore, impacts of climate change on forest health should be carefully evaluated. Given these assumptions, several fungal diseases on trees may become more devastating because of the following factors: (i) abiotic stresses, such as drought and flooding, are known to predispose trees to several pathogens; (ii) temperature and moisture affect pathogen sporulation and dispersal, and changes in climatic conditions are likely to favour certain pathogens; (iii) migration of pathogens triggered by climatic change may increase disease incidence or geographical range, when pathogens encounter new hosts and (or) new potential vectors; and (iv) new threats may appear either because of a change in tree species composition or because of invasive species. If infection success is dependent on temperature, higher mean temperatures may lead to more attacks. Pathogens that have been of importance in southern Europe may spread northward and also upward to mountains. Pathogens with evolutionary potential for greater damage should be identified to estimate the magnitude of the threat and to prepare for the changing conditions. A review of the above-mentioned cases is presented. Some priorities to improve the ability to predict impacts of climate change on tree diseases are discussed.
doi: 10.1080/07060661.2008.10540534
Keywords: Drought; epidemiology; forest diseases; Global change; Global warming; opportunistic fungi; pathogenic fungi; predisposition; review; Temperature; water stress

DESERTIFICATION–A NEW SECURITY CHALLENGE FOR THE MEDITERRANEAN? Policy agenda for recognising and coping with fatal outcomes of global - Brauch, H. G. (Desertification in the Mediterranean Region. A Security …, 2006)
Desertification (representing soil degradation) is one of the three nature-induced (climate change, hydrological cycle) and of three primarily human-induced challenges (population growth, urbanisation and food) of global environmental change. These six components closely interact and contribute to fatal outcomes: primarily to extreme weather events and hydro-meteorological disasters (drought, flash floods, storms) and environmentally-induced migrations. These two fatal outcomes may have – in some cases – societal repercussions that may trigger or contribute to domestic, regional and international crisis and conflicts and thus they may become an issue of both human, societal, national and international security. To illustrate the causal linkages: for example in Morocco in the 1980s and 1990s, the following chain of events could be observed: severe drought, increase in food prices, hunger riots, general strikes, the police and armed forces interfered to repress these violent upheavals and subsequently hundreds of casualties could be deplored. These cases were not listed as a conflict in the relevant conflict data bases. The paper is organised in three parts: In the first part, the complex casual interactions among six factors of global environment change, two fatal outcomes and three societal repercussions: crises, conflicts and conflict avoidance, prevention and resolution will be discussed. In the second part, different security concepts will be reviewed that may be of relevance for dealing with desertification as a security issue. In the third part, possible security relevance pro-active political strategies will be considered, to avoid, and prevent that desertification issues can pose security challenges, and to contribute to a resolution of the desertification driven violence. 11
The following values have no corresponding Zotero field: periodical: Desertification in the Mediterranean Region. A Security …
Keywords: conflict; desertification; Drought; environmental degradation; environmental security; food security; Global change; human security; Land degradation; migration; natural disasters (voyant)

DESERTIFICATION–A NEW SECURITY CHALLENGE FOR THE MEDITERRANEAN? Policy agenda for recognising and coping with fatal outcomes of global - Brauch, H G (Desertification in the Mediterranean Region. A Security …, 2006)
Desertification (representing soil degradation) is one of the three nature-induced (climate change, hydrological cycle) and of three primarily human-induced challenges (population growth, urbanisation and food) of global environmental change. These six components closely interact and contribute to fatal outcomes: primarily to extreme weather events and hydro-meteorological disasters (drought, flash floods, storms) and environmentally-induced migrations. These two fatal outcomes may have – in some cases – societal repercussions that may trigger or contribute to domestic, regional and international crisis and conflicts and thus they may become an issue of both human, societal, national and international security. To illustrate the causal linkages: for example in Morocco in the 1980s and 1990s, the following chain of events could be observed: severe drought, increase in food prices, hunger riots, general strikes, the police and armed forces interfered to repress these violent upheavals and subsequently hundreds of casualties could be deplored. These cases were not listed as a conflict in the relevant conflict data bases. The paper is organised in three parts: In the first part, the complex casual interactions among six factors of global environment change, two fatal outcomes and three societal repercussions: crises, conflicts and conflict avoidance, prevention and resolution will be discussed. In the second part, different security concepts will be reviewed that may be of relevance for dealing with desertification as a security issue. In the third part, possible security relevance pro-active political strategies will be considered, to avoid, and prevent that desertification issues can pose security challenges, and to contribute to a resolution of the desertification driven violence. 11
Keywords: conflict; desertification; Drought; environmental degradation; environmental security; food security; Global change; human security; Land degradation; migration; natural disasters (voyant)

Influence of increased atmospheric CO2 concentration on quality of plant material and litter decomposition - Coûteaux, Marie-Madeleine; Kurz, Cathy; Bottner, Pierre; Raschi, Antonio (Tree Physiology, 1999)
Nitrogen (N) and lignin concentrations in plant tissues and litter of plants grown in greenhouses or open-top chambers in elevated atmospheric CO2 concentration were compared with those of plants grown in ambient air in short-term studies. We also compared the N concentration of plant material of Quercus ilex L. and Q. pubescens Willd. growing in the vicinity of natural CO2-springs with that of the same species growing at a control site. In the short-term studies, elevated CO2 caused significant decreases in tissue N concentration and the extent of the decrease varied with species. Nitrogen amendment of the soil lessened the CO2-enrichment effect. Lignin concentration was modified by elevated CO2 and the effect was species specific, but no general positive or negative trend was evident. A comparison of trees growing under natural conditions near a natural CO2-spring and at a control site revealed no site differences in N concentration of the plant material. A comparison of published results on decomposition rates of litter produced in elevated atmospheric CO2 and in ambient air indicated that CO2 enrichment can cause both enhancements and decreases of carbon mineralization. We conclude that (1) long-term responses to elevated CO2 could differ from the results obtained from short-term studies and that (2) biodiversity could be an important factor altering the sign of the feedback on atmospheric CO2 concentration. We also discuss the implications of our finding of a long-term, inhibitory effect of the initial N concentration of litter on the decomposition rate of litter and its consequence on ecosystem feedback.
10.1093/treephys/19.4-5.301
Keywords: Biodiversity; Carbon dioxide; Global change; lignin content; nitrogen content

Influence of increased atmospheric CO2 concentration on quality of plant material and litter decomposition - Coûteaux, Marie-Madeleine; Kurz, Cathy; Bottner, Pierre; Raschi, Antonio (Tree Physiology, 1999)
Nitrogen (N) and lignin concentrations in plant tissues and litter of plants grown in greenhouses or open-top chambers in elevated atmospheric CO2 concentration were compared with those of plants grown in ambient air in short-term studies. We also compared the N concentration of plant material of Quercus ilex L. and Q. pubescens Willd. growing in the vicinity of natural CO2-springs with that of the same species growing at a control site. In the short-term studies, elevated CO2 caused significant decreases in tissue N concentration and the extent of the decrease varied with species. Nitrogen amendment of the soil lessened the CO2-enrichment effect. Lignin concentration was modified by elevated CO2 and the effect was species specific, but no general positive or negative trend was evident. A comparison of trees growing under natural conditions near a natural CO2-spring and at a control site revealed no site differences in N concentration of the plant material. A comparison of published results on decomposition rates of litter produced in elevated atmospheric CO2 and in ambient air indicated that CO2 enrichment can cause both enhancements and decreases of carbon mineralization. We conclude that (1) long-term responses to elevated CO2 could differ from the results obtained from short-term studies and that (2) biodiversity could be an important factor altering the sign of the feedback on atmospheric CO2 concentration. We also discuss the implications of our finding of a long-term, inhibitory effect of the initial N concentration of litter on the decomposition rate of litter and its consequence on ecosystem feedback.
10.1093/treephys/19.4-5.30110.1093/treephys/19.4-5.301
Keywords: Biodiversity; Carbon dioxide; Global change; lignin content; nitrogen content

Seasonal embolism and xylem vulnerability in deciduous and evergreen Mediterranean trees influenced by proximity to a carbon dioxide spring - Tognetti, Roberto; Longobucco, Anna; Raschi, Antonio (Tree Physiology, 1999)
We investigated how proximity to natural CO2 springs affected the seasonal patterns of xylem embolism in Quercus ilex L., Quercus pubescens Willd., Fraxinus ornus L., Populus tremula L. and Arbutus unedo L., which differ in leaf phenology and wood anatomy. Xylem embolism was evaluated in both artificially dehydrated branches and in hydrated apical branches collected at monthly intervals during a 20-month sampling period. Initial specific hydraulic conductivity was also evaluated. We found species-dependent differences in xylem hydraulic properties in response to elevated CO2 concentration. Populus tremula was the most embolized and A. unedo was the least embolized of the species examined. Effects of elevated CO2 were significant in Q. pubescens, P. tremula and A. unedo, whereas the overall response to elevated CO2 was less evident in F. ornus and Q. ilex. Specific hydraulic conductivity differed among species but not between sites, although the interaction between species and site was significant. Differences in xylem vulnerability between trees growing near to the CO2 spring and those growing in control areas were small. Although differences in hydraulic properties in response to elevated CO2 concentration were small, they may be of great importance in determining future community composition in Mediterranean-type forest ecosystems. The possible causes and ecological significance of such differences are discussed in relation to elevated CO2 concentration and other environmental conditions.
10.1093/treephys/19.4-5.271
Keywords: cavitation; CO2 springs; diffuse-porous; Global change; hydraulic conductivity; Mediterranean-type ecosystems; ring-porous; semiring-porous

Long term effects of naturally elevated CO 2 on mediterranean grassland and forest trees - Körner, C; Miglietta, Francesco (Oecologia, 1994)
We investigated the carbon supply status in species-rich mediterranean plant communities growing in a bowl-shaped 1-ha "CO2 spring" area near Sienna, Italy. A geothermic "lime-kiln" has provided these communities, for as long as historical records are avail- able, with pure CO2 that mixes with ambient air at canopy level to daytime means of 500-1000 ppm CO2. Immediately outside the spring area similar plant com- munities are growing on similar substrate, and in the same climate, but under ca. 355 ppm CO2. We found no evidence that plants in the CO2 spring area grow faster, flower earlier or become larger. However, we found very large differences in tissue quality among the 40 species studied inside and outside the spring area. Depending on weather conditions, the mean concentra- tion of total non-structural carbohydrates (TNC, sugars and starch) in leaves of herbaceous plants was 38-47% higher in the spring area. Fast growing ruderals growing on garden soil inside and outside the spring area show the same response. Among trees, leaves of the deciduous Quercus pubscens contain twice as much TNC inside as outside the vent area, whereas evergreen Q. ilex leaves show no significant difference. TNC levels in branch wood paralleled leaf values. TNC in shade leaves was also higher. Elevated CO2 had no effect on the sugar fraction, therefore differences in TNC are due to starch accumulation. Leaf nitrogen concentration decreases under elevated CO2. These observations suggest that the commonly reported TNC accumulation and N depletion in leaves growing under elevated CO2 are not restricted to the artificial condi- tions of short-term COz enrichment experiments but persist over very long periods. Such an alteration of tissue composition can be expected to occur in other plant communities also if atmospheric COz levels con- tinue to rise. Effects on food webs and nutrient cycling are likely
Keywords: carbohydrates; Global change; leaf nitrogen; natural-co2 springs; photosynthesis